The crustose red algal genus Peyssonnelia (Peyssonneliales, Rhodophyta) in the Azores : from five to one species - Gabriel, Daniela (2015)
The family Peyssonneliaceae comprises a worldwide group of non-calcified to calcified, crust-forming red algae of great ecological significance. Of the genera currently recognized in the family, Peyssonnelia has been widely considered to contain the largest number of species, with five members reported for the Azores. Using rbcL as a molecular marker, we here report on the taxonomic identity of recent collections of Peyssonneliaceae from the Azorean islands of São Miguel, Graciosa and Pico, and compare those specimens in a worldwide context. Only a single Peyssonnelia species, P. squamaria, is confirmed for the Azorean archipelago, with three different haplotypes. Although the populations in the Azores are genetically different from those occurring in the Mediterranean, this separation appears to be relatively recent.